2005
DOI: 10.1097/01.ico.0000138836.45070.0f
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Corneal Thickness Values in Postmenopausal Women With Dry Eye

Abstract: Postmenopausal women with dry eye have lower corneal thickness values than postmenopausal women without dry eye. Special care must be taken with these reduced corneal thickness values when selecting postmenopausal women for surgery involving corneal photoablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…12 Although there is little documentation about the CCT changes in postmenopausal women, SanchisGimeno JA et al demonstrated that CCT was lower in postmenopausal women with dry eye symptoms compared to postmenopausal women without dry eye symptoms. 13 This finding suggests that, in postmenopausal women, dry eye may also has an additional effect on the decrease in CCT. A randomized controlled study investigating menopausal women indicated that no significant corneal curvature changes were detected between premenopausal and postmenopausal women and estrogen established a significant negative correlation with horizontal curvature in postmenopausal women but estrogen did not correlate with the corneal curvature changes in premenopausal women and progesterone did not correlate with the corneal curvature changes both in pre-and postmenopausal women.…”
Section: Discussionmentioning
confidence: 68%
“…12 Although there is little documentation about the CCT changes in postmenopausal women, SanchisGimeno JA et al demonstrated that CCT was lower in postmenopausal women with dry eye symptoms compared to postmenopausal women without dry eye symptoms. 13 This finding suggests that, in postmenopausal women, dry eye may also has an additional effect on the decrease in CCT. A randomized controlled study investigating menopausal women indicated that no significant corneal curvature changes were detected between premenopausal and postmenopausal women and estrogen established a significant negative correlation with horizontal curvature in postmenopausal women but estrogen did not correlate with the corneal curvature changes in premenopausal women and progesterone did not correlate with the corneal curvature changes both in pre-and postmenopausal women.…”
Section: Discussionmentioning
confidence: 68%
“…As such, to our knowledge, this is the first study that evaluates the proliferative response to desiccating stress and the thickening of the corneal epithelium, and suggests that abnormally rapid tissue turnover and hyperplasia is a common response to the epithelial “stress response” throughout the entire ocular surface. Previous studies in humans have focused on total corneal, not just epithelial, thickness, and have reported a reduction in central corneal thickness in Sjögren’s and non Sjögren’s dry eye; in these studies the central thickness of the corneal epithelium did not change (Erdélyi et al, 2007; Tuominen et al, 2003) or was not evaluated (Liu and Pflugfelder, 1999; Sanchis-Gimeno et al, 2005; Villani et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…11 We enrolled the control subjects, who were at similar age and have similar distribution of sex with the RA group, and Scheimpflug imaging was performed preceding the corneal staining. In addition, there was no significant effect of age or gender on any of the pachymetric [15][16][17] Some other studies demonstrate thickening in cornea following artificial tears or topical cyclosporine-A treatments. 18,19 Villani et al 9 found the corneas of RA patients to be significantly thinner than those of control subjects in their in vivo confocal study.…”
Section: Discussionmentioning
confidence: 95%